Factors influencing young consumers’ purchase intention of organic food product / Aynul Haydirah Ayub, Yusrina Hayati Nik Muhammad Naziman and Muhammad Faizal Samat - Ayub, Aynul Haydirah; Nik Muhammad Naziman, Yusrina Hayati; Samat, Muhammad Faizal (Faculty of Business and Management, Universiti Teknologi MARA, Shah Alam, Malaysia, 2018)
Research findings on buying behaviour towards organic food product are still inconsistent. Therefore, this study aims to examine a significant relationship between environmental consciousness, health consciousness and social influence and young consumers’ purchase intention towards organic food product. The total of 150 questionnaires was designed and distributed at the public area of Kerteh, Terengganu. In return only 140 questionnaires were returned and usable. The result of the analysis showed that environmental consciousness is the most significant factor to influence young consumer purchase intention towards organic food product. Health consciousness and social influence on the other hand, showed a result as have no significant relationship in determined a factor that influencing young consumer purchased intention towards organic food product. In these relations, marketer and future researchers should see the important factor to explore the opportunities to cater for this market segment in future.